2019
DOI: 10.1007/s13410-019-00716-3
|View full text |Cite
|
Sign up to set email alerts
|

A community-based cross-sectional study of magnitude of dysglycemia and associated factors in Southwest Ethiopia

Abstract: Background Diabetes, one of the non-communicable diseases becoming major public health problems in the country, is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia of diabetes is associated with long-term damage, dysfunction, and failure of different organs, especially the eyes, kidneys, nerves, heart, and blood vessels. This study aimed at assessing the prevalence of dysglycemia (type 2 diabetes and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…In the present study, the magnitude of prediabetes was 14.5% (95% CI: 11.1–18.1). This finding was supported by research conducted in Mizan-Aman, southern Ethiopia (15.9%) [ 34 ], Dessie, northeast Ethiopia (15.7%) [ 24 ], Koladiba, northwest Ethiopia (12%) [ 26 ], and Bahir Dar, northwest Ethiopia (12.9%) [ 22 ], Jimma, southwest Ethiopia (12.9%) [ 38 ], Augsburg, Germany (16.4%) [ 53 ], Qatar (12.5%) [ 44 ], and Pakistan (14.4%) [ 46 ]. However, this result is lower than that of research conducted in Ningbo, China (28.5%) [ 54 ], Texas, USA (32%) [ 52 ], and Bangladesh (22.4%) [ 47 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the present study, the magnitude of prediabetes was 14.5% (95% CI: 11.1–18.1). This finding was supported by research conducted in Mizan-Aman, southern Ethiopia (15.9%) [ 34 ], Dessie, northeast Ethiopia (15.7%) [ 24 ], Koladiba, northwest Ethiopia (12%) [ 26 ], and Bahir Dar, northwest Ethiopia (12.9%) [ 22 ], Jimma, southwest Ethiopia (12.9%) [ 38 ], Augsburg, Germany (16.4%) [ 53 ], Qatar (12.5%) [ 44 ], and Pakistan (14.4%) [ 46 ]. However, this result is lower than that of research conducted in Ningbo, China (28.5%) [ 54 ], Texas, USA (32%) [ 52 ], and Bangladesh (22.4%) [ 47 ].…”
Section: Discussionsupporting
confidence: 54%
“…The present magnitude of undiagnosed diabetes was 4.5% (95% CI: 2.9–7.4). This finding was in line with those of studies conducted in Mizan-Aman,southwest Ethiopia (5.8%) [ 34 ]; Dessie, northeast Ethiopia (4.9%) [ 24 ]; Gilgel Gibe, southwest Ethiopia (3.8%) [ 35 ]; Gondar, northwest Ethiopia (3.5%) [ 36 ]; Dire Dawa, eastern Ethiopia (6.2%) [ 20 ]; Dabat, northwest Ethiopia (5.1%) [ 37 ]; Jimma, southwest Ethiopia (5.7%) [ 38 ]; Bishoftu, Ethiopia (5%) [ 39 ]; South Africa (3.3%) [ 40 ]; Henan, China (4.2%) [ 41 ]; Quebec, Canada (6.2%) [ 42 ]; Tehran, Iran (5.1%) [ 43 ]; Qatar (5.9%) [ 44 ]; Punjab, India (6.8%) [ 45 ]; Pakistan (7.1%) [ 46 ]; and Bangladesh (5.4%) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies were identified that provided evidence on the risk of T2DM among the general population. Ten of the studies were population/community-based cross-sectional studies [38][39][40][41][42][43][44][45][46][47], two were hospital-based case-control studies [48,49], and one study was a comparative cross-sectional study [50]. A total of 14,432 participants from the ten cross-sectional studies and the two hospital-based case-control studies were used for meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies conducted in Gondar, northwest Ethiopia, showed that 2.3% of the individuals lived with undiagnosed DM 15. Factors such as educational level, body mass index (BMI), family history and the presence of other chronic illnesses have been associated with undiagnosed DM 10 16–20. In addition, low health-seeking behaviour, like lack of regular health check-ups, also contributed to undiagnosed diabetes.…”
Section: Introductionmentioning
confidence: 99%